Drivers of vulnerability to climate change and adaptive responses of forest-edge farming households in major agro-ecological zones of Nigeria (2022)
An understanding of forest communities’ risk factors for climate variation, adaptation trajectories, and how agroecological differences shape their responses are critical to future policy formulation in Nigeria. Therefore, drivers of vulnerability to climate change and adaptation options of forest communities’ farming households in major agro-ecological zones of Nigeria were investigated. Data were collected, using an interview schedule, from 183 forest-edge households in savanna, mangrove, and rainforest agro-ecologies. Descriptive statistics and analysis of variance were used to analyse the data. Respondents cultivated 6.4 ± 2.6 acres of farmland. Changes in rainfall patterns were most experienced in the rainforest and savanna whereas, it was temperature fluctuation in the mangrove. Crop farming was the worst hit by climate change among other livelihoods. Crop rotation in the savanna and mangrove (X = 2.12; 2.44, respectively), and mixed farming in the rainforest (X = 2.52) were top adaptation priorities while crop insurance was the least. Low paying livelihood alternatives (X = 1.54), illiteracy (X = 1.73), and lack of infrastructure (X = 1.38) were major social vulnerability drivers of climate change in the savanna, mangrove, and rainforest, respectively. Major political and economic drivers were inconsistent government policy and poverty, respectively. The use of adaptation measures was not significantly different in the agro-ecologies, whereas, the livelihood impact of climate change was (F = 9.990; p < 0.05). Social and environmental drivers of vulnerability to climate change differ in the forest communities, and adaptation priorities varied according to zones